ANALISIS BREAK EVENT POINT (BEP) SEBAGAI ALAT PERENCANAAN LABA PADA INDUSTRI MINUMAN KESEHATAN ( STUDI KASUS : JAHE INSTAN PUTRI KELURAHAN TIMUR INDAH KOTA BENGKULU ) - Romzi -; Jusuf Wahyudi; Yossie Yumiati (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2014)
Break Event Point (BEP) Analysis or break-even analysis is a technique for studying the relationship of total cost, expected profit and sales volume. Through the break-even point analysis the company's can make a planning profit in order to obtain information about how much sales could be increased or decreased so the company does not lose. The purpose of this study is to investigate how the production and sales of instant ginger princess in order to achieve the BEP and to investigate the use of BEP analysis in relation to the profit planning. This study uses a case study in health instant ginger beverage industry, located in Kelurahan Timur Indah Kota Bengkulu. The study was conducted in August 2012 that used are primary data and secondary data. Primary data taken based on interviews and observations by questionnaire, while secondary data taken based on the study of literature and the internet. Analytical technique used is the analysis of BEP followed by calculation of profit planning using the analysis of cost-volume-profit. Based on the survey results revealed that the health drink industry of ginger instant of Putri in Kelurahan Timur Indah Kota Bengkulu should produce instant ginger at 1,887.37 kg per year to reach the BEP with a sales value of Rp. 94,368,000, - per year. The results of the BEP analysis related to profit planning used Cost- Volume-analysis equation where this health drink industry can be increased from Rp. 31,631,333.33 to Rp. 40,000,000.- by increasing of the sales volume from 2,520 kg per year to 2,683.53 kg. Based on calculations that the instant ginger of Putri is quite profitable with a value gain Rp. 31.631.333,33, - per year. Profit planning can be done by considering the profit margin of safety calculation, where the company was only able to decrease the volume of sales by 29.78% in order not to suffer any loss.Keywords : BEP, profit, Margin of safety